The Effects of Networks on New Entrepreneur’s Internationalization, a Case Study from Izmir-Turkey - Goztas, Aylin; Dincer Yarkin; Fusun Topsumer; Ozlem Cosan; Nuket Aygen (European Journal of Multidisciplinary Studies, 2017)
Entrepreneurship is not only one of the important topics of developed countries but also takes place in developing countries. State and government agencies, as well as private sector representatives spend efforts for increasing the number of entrepreneurs in an economy. Thus, it is expected to decrease unemployment rates, prevent unrecorded economy and accelerating innovation capability of a nation. To achieve these goals, it is crucial to understand who the entrepreneur is, how their potential will be brought out, what kind of support does he/she need. Especially in emerging economies, entrepreneurs should have vision of being international to gain competitive advantage. Because of that reason researches on internationalization of new ventures have been intensified for 20 years. After experiencing and observing the role of networks and networking on sustainable entrepreneurship, number of studies have been increased. In this study, we chose to conduct in depth interviews among the companies who are in business less 5 years and having an export percentage 10 percent in accordance with total sales. The findings of the research show that networking accelerates internationalization of new ventures.